Implementasi Kepemimpinan Transformasional dalam Menanamkan Budaya Organisasi Era Digitalisasi Pendidikan Dasar - Azzukhrufi, Jaya Roza; Santoso, Subhan Adi; Hadi, Alfiyan Fikri (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2026)
This research examines how transformational leadership is implemented to instill organizational culture in the digitalization era of elementary education and how it impacts classroom learning. Using a qualitative method with a descriptive-qualitative approach, the study produces descriptive data in the form of written or spoken words from participants and observable behavior. The findings highlight key aspects: Transformational Leadership, Digital School Implementation, Digital Organizational Culture, and the Improvement of Teacher Performance and Learning Quality. Transformational leadership supports the development of an adaptive, collaborative, and innovative school culture. The principal, acting as a transformational leader, not only sets a digital vision but also internalizes it into the school’s values, norms, and work habits. As a result, the organizational culture shifts from bureaucratic work patterns toward a continuous learning culture within a learning organization that is responsive to technological change. Transformational leadership is positioned not merely as a leadership style, but as a mechanism for embedding digital values into elementary school culture. This expands the concept beyond motivation and performance, emphasizing the formation of a digitally adaptive organizational culture. Ultimately, the study formulates an elementary school organizational culture that integrates traditional religious values with technological innovation.